Associations among parent–child relationships and cognitive and language outcomes in a clinical sample of preschool children. Issue 2 (17th February 2017) - Leiser, Kara; Heffelfinger, Amy; Kaugars, Astrida
Abstract: Objective: To examine associations among parent–child relationship characteristics and child cognitive and language outcomes.Methods: Preschool children ( n  = 72) with early neurological insult completed assessments of cognitive and language functioning and participated in a parent–child semi-structured interaction.Results: Quality of the parent–child relationship accounted for a significant amount of unique variance (12%) in predicting children's overall cognitive and language functioning. Impact of neurological insult was a significant predictor.Conclusions: Caregiver–child interactions that are harmonious and reciprocal as evidenced by affective and/or verbal exchanges support children's cognitive and language development. Observations of interactions can guide providers in facilitating child- and family-centered interventions.